A magyar felsőoktatás egy fontos intézménycsoportja a királyi jogakadémiák forrásai és feldolgozásának lehetőségei (1777-1850) - Juhász, Réka (Gerundium, 2016)
AN IMPORTANT INSTITUTIONAL CLUSTER OF HIGHER EDUCATION IN HUNGARY: THE SOURCES SUPPLIED BY THE ROYAL ACADEMIES OF LAW AND THE PROCESSES OF THEIR CATALOGUING, (1777–1850). he main objective of this study is to ofer an overview of the currently available sources which are extant regarding the peculiar institutions and student population of higher education of the 18th and 19th centuries in Hungary. On surveying the types of sources, it takes stock of the material which is currently accessible to assess the one-time student population of the royal academies of law in Pozsony, Győr, Kassa, Nagyvárad, as well as of the similar royal institutions of Zágráb and the royal lyceum in Kolozsvár. Surveys of this type have demonstrated that in the irst half of the 19th century almost 50,000 students enrolled in these types of institutions. his number by itself tends to indicate that these institutions may have fulilled a much larger role in educating a Hungarian intelligentsia in the Reform Age than one would assume on the basis of a lower-thanuniversity academic level of these institutions.